Handbook of urban inequalities - Mahadevia, Darshini (Oxford India handbooks, 2012)
"Nearly all urban data used for the purpose of economic analysis, urban policymaking, and investment decision-making are aggregated data. Urban systems, however, are heterogeneous and complex, which requires more nuanced responses. This handbook reprocesses NSS household-level schedules to develop disaggregated data sets for different size classes of urban centres. Comparing changes in the pre-reform and post-reform periods, the book analyses the inequalities between metros and non-metros with regard to consumption, poverty, employment, education levels, and services. With detailed and meticulous data analysis covering the last 25 years, the book covers: The importance of small and medium towns (SMTs) in urban development and urban poverty trends across major states in India. Head Count Ratio (HCR) and per capita monthly consumption expenditures for different size class of urban centres in 16 major states in India. Employment patterns and unemployment levels across different size classes and disaggregated by sex. Level of basic facilities in different size classes of urban centres pertaining to water supply, sanitation, and garbage collection; and Patterns of urban inequalities and their policy implications."--Publisher's website.